Constitution as a prognostic factor in medical and sports anthropology - Nikitjuk, B. A. (Array, 1990)
In the 1980s there is a growing demand for scientific approach to health protection and sport. The coming ecological crisis, load intensification in some branches of industry and sports have revealed the human vulnerability to outer influences and scantiness of protective mechanisms. A thorough study of the constitution problem, using genetic markers for directed selection of those people who can retain their capacity in extreme conditions, may help to preserve people's health and strength. Practical requirements have led to the inclusion of some dermatoglyphic values, blood groups into the list of constitutionally significant features. These new approaches are useful for the selection of new ways of solving existing scientific problems. While somatotypological affiliation makes the evaluation of body structure easier, taking into account the